SISTEM APLIKASI PENGOLAHAN NILAI KEDISIPLIAN SISWA BERBASIS WEB MENGGUNAKAN METODE FUZZY LOGIC TSUKAMOTO - Mar’atus Sholichah; Reza Augusta Jannatul Firdaus; Aries Dwi Indriyanti; Zein Vitadiar, Tanhella (Inovate, 2024)
One of the most important aspects of student assessment is descipline which measures several indicatorssuch as attendance or participation in school activities and also compliance with the rules set by the school.The fuzzy logic Tsukamoto method was chosen because of its ability to handle uncertain and subjectivedata so and objective student discipline assessment reports. The system is designed using websitetechnology that makes it easy for teachers to enter, monitor and evaluate student discipline scores. Systemtesting is carried out using data obtained from the superior NU Mojoagung Madrasah Ibtidaiyah, data inthe from of assessments used by teachers to determine student discipline such as attendance and attitudescores which are processed using the Tsukamoto fuzzy logic method. The results of this study show thatthis system is able to produce reports on the discipline assessment of students who are disciplined by 55%and those who are quite disciplined 45% of a certain period of time with a good level of accuracy so that itcan facilitate the school in a more precise evaluation related to coaching and developing student discipline.Keywords: Processing Scores, Discipline, Fuzzy.